ANALISIS PROSES METAKOGNISI DALAM PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI GAYA KOGNITIF - Sili, Isabela Freningsi Kidi; Argarini, Dian Fitri (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2018)
The purpose of this research was to determine the metacognition process of students in Baiturrohmah Malang Islamic Junior High School Class VIII which have a field dependent (FD) and field independent (FI) cognitive style in solving mathematical problems in solid geomethry topic. This type of research is qualitative descriptive research with purposive sampling method. The subject were 1 FD and 1 FI. The subjects were selected by GEFT test. The instrumentsused in this research are broblem solving test and interview guidelines. The resultsare (1) the process of metacognition of FD subject in problemsolving, on awareness indicator, it can be seen that subject was able to mention what was ask of the question completely, subject was mistaken in writing down what was known. On regulating indicator the subject has been able to determine the plan and carry out the plan correctly. The indicator evaluating the subject has been able to re-examine the answers and give the conclusion, (2) the process of metacognition of FI subject in problem solving. In the awareness indicator, it can be seen that subject has been able to mention what is known and asked about the problem well. Regulating indicatorthe subject was able to arrange the plan and carry out the plan correctly. evaluating indicator the subject has not been able to re-examine the answer that have been done but have not arrived at conclusions.